2020
DOI: 10.3390/ijms21239263
|View full text |Cite
|
Sign up to set email alerts
|

AGE-RAGE Axis Stimulates Oxidized LDL Uptake into Macrophages through Cyclin-Dependent Kinase 5-CD36 Pathway via Oxidative Stress Generation

Abstract: Advanced glycation end products (AGEs) are localized in macrophage-derived foam cells within atherosclerotic lesions, which could be associated with the increased risk of atherosclerotic cardiovascular disease under diabetic conditions. Although foam cell formation of macrophages has been shown to be enhanced by AGEs, the underlying molecular mechanism remains unclear. Since cyclin-dependent kinase 5 (Cdk5) is reported to modulate inflammatory responses in macrophages, we investigated whether Cdk5 could be inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 57 publications
1
18
0
Order By: Relevance
“…The floating cells were seeded onto 24-well dishes and incubated with 40 ng/mL PMA in RPMI 1640 medium containing 10% FCS at 37 • C in a humidified atmosphere with 5% CO 2 for 24 h. After twice rinsing gently by phosphate-buffer saline (PBS), adherent cells were prepared as differentiated macrophages. Previously, the adherent cells used like this experiment were differentiated from monocytes to macrophages by analysis of fluorescence-activated cell sorting (FACS) [25,32,[36][37][38][39][40]. U937 macrophages were treated with or without 1 nmol/L [D-Ala 2 ]GIP, or 0.215 µmol/L (R)-DRF053 in RPMI 1640 medium including 10% FCS at 37 • C in 5% CO 2 for 18 h.…”
Section: Experiments Of U937 Macrophagesmentioning
confidence: 99%
See 3 more Smart Citations
“…The floating cells were seeded onto 24-well dishes and incubated with 40 ng/mL PMA in RPMI 1640 medium containing 10% FCS at 37 • C in a humidified atmosphere with 5% CO 2 for 24 h. After twice rinsing gently by phosphate-buffer saline (PBS), adherent cells were prepared as differentiated macrophages. Previously, the adherent cells used like this experiment were differentiated from monocytes to macrophages by analysis of fluorescence-activated cell sorting (FACS) [25,32,[36][37][38][39][40]. U937 macrophages were treated with or without 1 nmol/L [D-Ala 2 ]GIP, or 0.215 µmol/L (R)-DRF053 in RPMI 1640 medium including 10% FCS at 37 • C in 5% CO 2 for 18 h.…”
Section: Experiments Of U937 Macrophagesmentioning
confidence: 99%
“…The U937 cells were treated with 10 µg/mL Dil-ox-LDL in RPMI 1640 medium including 10% FCS at 37 • C in 5% CO 2 for 18 h [25,32,36]. After twice washing with PBS gently, immunofluorescence was observed using Keyence BZ-X710 microscope and analyzed with the Keyence BZ-X710 software (Osaka, Japan).…”
Section: Dil-ox-ldl Uptake Into Macrophagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, they concluded that this new compound does not increase the inflammatory response in the analyzed population of monocytes/macrophages and does not affect the dentin regeneration in which MMP-2 and MMP-9 are normally involved. The participation of macrophages/foam cells in the development of atherosclerosis was described by Yashima et al [ 19 ]. Advanced glycation end products (AGEs) localize to macrophage-derived foam cells within atherosclerotic lesions, which is associated with a higher risk of atherosclerotic cardiovascular disease under diabetic conditions.…”
mentioning
confidence: 99%